(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today, innovation is developing quickly and giving all fundamental and compelling answers for each prerequisite. Present days heaps of cases seen of missing Women. The Women are missing have ages between 14 to 17.Parents are stressed over Women. The paper clarifies about an android application which is utilized to follow the missing ladies. These days heaps of cell phone clients have an android telephones. The application works with the assistance of android portable. The android application dependents on GPS and SMS administrationsin Android portable. The GPS administration is utilized for following accurate area of Women. The GPS and GSM based frameworks are utilized to follow the area of Women. There are two different ways that can an application works. First is GPS based that is identified with the Location administrations and second is notice based which is identified with the Network administration. In the event that Location based administrations not working, the application utilizes Network based administrations which can have the option to send and get messages. ESP32 camera is used to take image of the harasser and it is also used to send live video recordings to the parent side. MQTT protocol is used for high latency and bandwidth strength. This protocol is used to send high volumes of sensor messages. In this situation, our framework guarantees greatest security and guarantees live following for their children since parent stresses are certified. This undertaking proposed a model for ladieswellbeing through advanced mobile phones that gives the alternative to follow the area of their ladies just as in case of crisis ladies can send a snappy message and it’s present area by means of BLYNK application. This proposed framework is approved by testing on the Android stage utilizing IoT.